2010
DOI: 10.1371/journal.pone.0012234
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Associates with Notch1 Precursor to Maintain Notch1 Expression under a Stress Condition in Mouse Cells

Abstract: BackgroundMatricellular proteins, including periostin, modulate cell-matrix interactions and cell functions by acting outside of cells.Methods and FindingsIn this study, however, we reported that periostin physically associates with the Notch1 precursor at its EGF repeats in the inside of cells. Moreover, by using the periodontal ligament of molar from periostin-deficient adult mice (Pn−/− molar PDL), which is a constitutively mechanically stressed tissue, we found that periostin maintained the site-1 cleaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…These data suggest that mechanical strain will activate latent TGF-β and twist-1 nuclear translocation, resulting in periostin activation. Finally, periostin null mice submitted to experimental tooth movement showed an increased PDL cells death associated with a reduced expression of Notch-1 and its downstream effector Bcl-xl, known to play an important role in cell survival under stress condition [67,68]. These results suggest that periostin associates with Notch-1 to maintain its expression and subsequent signaling in order to enhance cell tolerance against the stress and protect them from death [68].…”
Section: Periostin Is Involved In Bone Strength and Response To Mechamentioning
confidence: 83%
See 2 more Smart Citations
“…These data suggest that mechanical strain will activate latent TGF-β and twist-1 nuclear translocation, resulting in periostin activation. Finally, periostin null mice submitted to experimental tooth movement showed an increased PDL cells death associated with a reduced expression of Notch-1 and its downstream effector Bcl-xl, known to play an important role in cell survival under stress condition [67,68]. These results suggest that periostin associates with Notch-1 to maintain its expression and subsequent signaling in order to enhance cell tolerance against the stress and protect them from death [68].…”
Section: Periostin Is Involved In Bone Strength and Response To Mechamentioning
confidence: 83%
“…In summary, these data show that periostin is a prosurvival protein, largely involved in cell response to environmental stress [61,63,68]. By binding to integrins or cell surface receptors, periostin can activate intracellular signaling pathways leading to inhibition of apoptosis through inactivation of caspases 3 and 9 and prosurvival signaling resulting in increased bone formation [12,61,66,73].…”
Section: Periostin Promotes Osteoblast Adhesion Differentiation Andmentioning
confidence: 85%
See 1 more Smart Citation
“…involved in numerous normal physiological processes, but are also closely associated with the pathological processes involved in the occurrence and development of cardiovascular diseases, asthma and tumors (16). Currently, the majority of studies indicate that the overexpression of periostin is associated with the malignancy grade of a cancer; however, other studies have reported that periostin may inhibit the invasion and metastasis of bladder cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The EMI domain, which is a small module rich in cysteine residues found in members of the EMILIN family, is a site for protein-protein interaction [11]. Periostin directly interacts with type I collagen [12][13][14], fibronectin [15], and Notch1 [16] through its EMI domain, with tenascin-C [15] and BMP-1 [17] through its fas I domains, and with laminin g2 though the nature of the interaction is yet unknown [18]. These periostin interactions with mainly extracellular matrix molecules firstly occur intracellularly [15].…”
Section: Introductionmentioning
confidence: 99%